Pulmonary sequestration: an uncommon presentation with acute chest pain - Jamhuri, Nur Syazwani; Hasnol Aidi, Aminuddin; Mohamad Ali, Nur Izzati; Bahtiar, Mohamad Syahiirul Afifi (Elsevier Ltd, 2022)
This is a case of 18-year-old teenager presented with acute left sided chest pain for five days. This was associated with intermittent cough, and loss of weight in two weeks. Diagnosis was made by computed tomography of thorax plus angiogram that showed infected left intralobar pulmonary sequestration with lung abscess. Sputum culture grew Pseudomonas aeruginosa. He completed 14 days of antibiotic and subjected to feeding artery embolization. The aim of this case report is to highlight on the uncommon presentation and the need of high index of suspicion of pulmonary sequestration with support by imaging findings.